(untitled) (قضايا سياسية, 2023)
We conclude that it is wrong to judge the future of political Islam as failure and decline after the blow that the Brotherhood’s rule received in Egypt. It is true that the military coup against Morsi put the movement in real distress, especially since the failure this time fell on the group that represents the head of the organization, and in the central state of the organization. However, political Islam still has strong elements inside and outside Egypt, and the political Islam movement will not end so easily. It will remain a movement supported by societal forces, states, and media, economic, and security institutions, which have vital interests in ensuring its continuation. Moreover, the organizations of political Islam, led by the Muslim Brotherhood, are diverse organizations with a deep-rooted intellectual and cultural background, and have their own connections, relationships, and external support. Therefore, it is not expected that political Islam will disappear so easily .